School knowledge of infectious diseases in schools: conducting surveillance and on-demand, symptomatic respiratory viral testing in a large pre-kindergarten–12th grade school district - Schuster, Jennifer E.; Chohdry, Tamoor T.; Young, Chris T.; Lee, Brian R.; Banerjee, Dithi; Sasidharan, Anjana; Almendares, Olivia M.; Kirking, Hannah L.; Porter, Janelle; Deliu, Anila; Tilsworth, Shannon; Selvarangan, Rangaraj; et al. (Frontiers in Public Health, 2024)
Background: Little data about acute respiratory illnesses (ARI) and respiratory virus circulation are available in congregate community settings, specifically schools. To better characterize the epidemiology of ARI and respiratory viruses in schools, we developed School KIDS (Knowledge of Infectious Diseases in Schools).Methods: School KIDS is a prospective, respiratory viral testing program in a large metropolitan school district (pre-kindergarten-12 th grade) in Kansas City, Missouri. During the 2022-2023 school year, all students and staff were eligible to participate in surveillance respiratory viral testing at school by submitting observed self-administered nasal swabs monthly. Participants could also submit a nasal swab for on-demand symptomatic testing when experiencing ≥1 ARI symptom, including cough, fever, nasal congestion, runny nose, shortness of breath, sore throat, and/or wheezing. Swabs were tested in a research laboratory using multipathogen respiratory polymerase chain reaction assays. Participants were evaluated for ongoing viral shedding by collecting two weekly nasal swabs (i.e., convalescent), following initial on-demand symptomatic testing. Participants were asked to complete an electronic survey to capture presence and type of ARI symptom(s) prior to collection of respiratory swabs.Results: From October 31, 2022 -June 29, 2023, School KIDS enrolled 978 participants, including 700 students, representing 3.4% of the district student population, and 278 staff members. Participants submitted a median of 6 surveillance, 1 symptomatic, and 2 convalescent specimens during the study period. A total of 6,315 respiratory specimens, including 4,700 surveillance, 721 on-demand symptomatic, and 894 convalescent specimens, were tested.Overall, virus was detected in 1,168 (24.9%) surveillance and 363 (50.3%) symptomatic specimens. Of the 5,538 symptom surveys sent to participants prior to scheduled surveillance testing, 4,069 (73.5%) were completed; ARI symptoms were reported on 1,348 (33.1%) surveys.Conclusions: Respiratory surveillance testing in schools is feasible and provides novel information about respiratory virus detections in students and staff attending school. Schools are an important community setting, and better knowledge of respiratory virus circulation in schools may be useful to identify respiratory virus transmission in the community and to assess the impact of effective infection prevention measures.